A new species of Chubutomys (Rodentia, Hystricognathi) from the late Oligocene of Patagonia and its implications on the early evolutionary history of Cavioidea sensu stricto - Pérez, María Encarnación (2012)
Cavioidea is represented today by Dasyproctidae (agouties), Cuniculidae (pacas), and Caviidae (cavies or ‘‘guinea pigs’’, maras, mocos, and capybaras). Cavioidea sensu stricto (Cavioidea s.s.) clusters the extant and extinct Caviidae together with a diverse assemblage of extinct taxa grouped in the family Eocardiidae. Recent phylogenetic analyses of this group based on morphological characters corroborated the monophyly of Cavioidea s.s., but retrieved a paraphyletic arrangement of ‘‘eocardiids’’ as successive sister taxa of the crown-group Caviidae. The late Oligocene (Deseadan South American Land Mammal Age, SALMA) record of Cavioidea s.s. is relevant because it represents the oldest occurrence of the group, represented only by very scarce materials of Asteromys punctus and Chubutomys simpsoni. New materials of Deseadan cavioids are of prime importance to understand the early evolution of this group. The locality of Punta Nava (northeastern Santa Cruz Province, Patagonia, Argentina) has yielded a fauna assigned to the Deseadan SALMA, but no rodent remains were known so far. A recent fieldwork in this locality provided the first findings of fossil caviomorphs, including remains of Cavioidea, Octodontoidea, Chinchilloidea, and Erethizontoidea. A new species of Cavioidea s.s. from this locality is here described, and its phylogenetic affinities are evaluated. This new cavioid from the Deseadan SALMA, and the reinterpretation of the morphology of Chubutomys simpsoni, provide new insights into the early diversification of Cavioidea s.s. The new species from the late Oligocene, and the high position of Chubutomys in the phylogeny, draw back the origin of all protohypsodont lineages of Cavioidea s.s. to the Deseadan SALMA. Furthermore, this suggests thatthe early evolution of Cavioidea s.s. occurred through a major diversification pulse larger than previously proposed.